2021
DOI: 10.3390/su13105667
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Contributions of Urban Light Rail Transit to the Sustainable Development of Addis Ababa

Abstract: Many of the existing urban transport infrastructures in developing African cities are challenged by the mobility demands of their ever-increasing population and increased vehicle capacity. To address these transportation challenges, the Federal government of Ethiopia through the Ethiopian Railway Corporation (ERC) constructed and operates the Addis Ababa light rail transit (AA-LRT). Currently, many other African cities are following in action. This study aims to assess the contributions to sustainable developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The European Conference of Ministers of Transport has defined light rail as a rail-borne form of transport that can be developed in stages ranging from the modern tram to a rapid transport system operating on its own right of way, be it underground, at ground level, or elevated [15,16]. Ideally, light rail is a form of railway urban transportation system, that is not a heavy traditional form of railways.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Conference of Ministers of Transport has defined light rail as a rail-borne form of transport that can be developed in stages ranging from the modern tram to a rapid transport system operating on its own right of way, be it underground, at ground level, or elevated [15,16]. Ideally, light rail is a form of railway urban transportation system, that is not a heavy traditional form of railways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ideally, light rail is a form of railway urban transportation system, that is not a heavy traditional form of railways. The interest for LRT systems in the whole world has been increased in the last years, and relevant projects have been conceived and therefore analyzed in Europe [15,17], Africa [16,18], Asia [19,20], Australia [21,22] or America [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…(5) The role of design in social innovation and SUD: This theme was included because architecture and planning also provided impulses for the discussion on social innovations [22]; unfortunately, there were no contributions on this subject. Figure 1 presents an overview of the topics addressed in our Special Issue, from which it can be seen that mobility and transportation are a task area that also fosters social innovation for SUD [13,17]. Finally, I would like to return to the general question: Does SUD need a transition from social to institutional innovation?…”
Section: Technological Innovation In Sudmentioning
confidence: 99%
“…South America remains a blind spot in our Special Issue. The themes range from smart cities [11][12][13] and heritage [4,14] to policy options for regions in transition [13,[15][16][17]. In my call for papers, I raised five specific questions to which the submitted papers made valuable contributions:…”
mentioning
confidence: 99%
“…A study in the Dallas-Fort Worth metropolitan area similarly found that rail transit stations positively impacted population density [16]. The light rail transit in Addis Ababa was perceived to have a high contribution concerning urban sustainability in various dimensions, i.e., economically, socially, and environmentally [17]. The new metro Line 4 in Rio de Janeiro was found to have significantly reduced the vehicle-kilometer traveled (VKT), energy consumption, and carbon emission [18].…”
Section: Property Value Upliftmentioning
confidence: 99%